MAISO, J. (2022): Desde la vida dañada. La teoría crítica de Theodor W. Adorno, Tres Cantos (Madrid): Akal. - Sucasas Peón, Juan Alberto (Daimon Revista Internacional de Filosofia, 2025)
Reseña de MAISO, J. (2022): Desde la vida dañada. La teoría crítica de Theodor W. Adorno, Tres Cantos (Madrid): Akal.